Model Pembelajaran Jigsaw Sebagai Salah Satu Strategi Pembelajaran PKn di Sekolah Dasar - I Ketut Ngurah Ardiawan; Putu Diah Kristina; I Gede Toni Swarjana (STAHN Mpu Kuturan Singaraja, 2020)
In essence, the learning model is an essential part of the learning process. The learning model is a whole series of teaching course beginning to end. Selection of the learning model requires consideration to be applied to learners. The jigsaw model is a cooperative model of learning that encourages students into a heterogeneous small group. A heterogeneous group is a study group made up of a mixed student, both sexes, races, religions, and different learning abilities. The model of jigsaw study implicates a learning process that can enhance students activation and creativity in establishing their opinions of the group. The application of the Jigsaw model with citizenship education has led to the renewal of the monotonous, conventional model of learning and carry out the meaning of citizenship educators Key words : Jigsaw,Cooperative, Heterogen, Citizenship